2000
DOI: 10.1103/physrevlett.85.4112
|View full text |Cite
|
Sign up to set email alerts
|

Optical Field-Induced Mass Transport inAs2S3Chalcogenide Glasses

Abstract: We report the observation of a photorefractivelike nonlinearity responsible for the formation of giant relief modulations in amorphous semiconductor glasses. The photoinduced softening of the matrix, formation of defects with enhanced polarizability, and their drift under the optical field gradient force is believed to be the origin of the mass transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
100
2
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(111 citation statements)
references
References 20 publications
7
100
2
1
Order By: Relevance
“…direct light-induced fabrication of surface relief (SR) by lateral mass transport on ChG films, have been widely studied for several selected composition, including As 0.4 S 0.6 , As 0.2 Se 0.8 , Se [9][10][11][12] and appropriate mechanisms were proposed recently [13,14]. More detailed study reveals the influence of chalcogen content on this process.…”
Section: Aq1mentioning
confidence: 99%
“…direct light-induced fabrication of surface relief (SR) by lateral mass transport on ChG films, have been widely studied for several selected composition, including As 0.4 S 0.6 , As 0.2 Se 0.8 , Se [9][10][11][12] and appropriate mechanisms were proposed recently [13,14]. More detailed study reveals the influence of chalcogen content on this process.…”
Section: Aq1mentioning
confidence: 99%
“…25,28 Figure 2 shows light-intensity dependence of the peakto-valley height h in anisotropic deformations in As 2 S 3 and Se. Naturally, h tends to increase with the absorbed dose ␣It, 16,25 which is proportional to the absorbed photon number, where ␣ is the absorption coefficient, I is the incident light irradiance, and t is the exposure time. Accordingly, in the figure, the light-intensity dependence is compared under fixed absorbed doses.…”
Section: A Anisotropic Deformationmentioning
confidence: 99%
“…In the previous studies, 16,22,23,25 As 2 S 3 films were deposited onto microscope slides, which were exposed to focused linearly polarized laser beams. It was demonstrated that an isotropic expansion appears at first, which gradually transforms to an anisotropic M-shaped deformation with exposure time.…”
Section: A Anisotropic Deformationmentioning
confidence: 99%
See 2 more Smart Citations